“Passion, Lament, Glory”: Baroque Music and Modern Social Justice Resonances - Davidson, Jane W. (Voices: A World Forum for Music Therapy, 2017)
Baroque religious music was composed and performed to stimulate devotion as well as the inspire passion through the theatricality of the religious ritual including the processional arrangements which worked in tandem with the performance practices based on strong emotional delivery. The current project aimed to re-imagine historical emotional affect through a pasticcio performance of Baroque works focused on the Easter Passion and Resurrection delivering the narrative with enactment. The project was also conceived to deliver broader social justice messages allied to displaced and misunderstood peoples of different religious and cultural backgrounds. In this paper, the audience is invited to spectate a performance of Passion, Lament, Glory, staged at St Paul’s Cathedral, Melbourne just before Easter 2017. They are invited to share in the background to the work and read about audience responses to the live performance. These responses are reflected upon in terms of the empathic, cathartic and applied outcomes of the performance on the audience.